Solitary ulcerated plaque on the face - an unusual presentation of cutaneous plasmacytosis? - Ana Marta António; João Vitor Alves; Ricardo Coelho; Elvira Bártolo (Sociedade Brasileira de Dermatologia, 2017)
Abstract Cutaneous and systemic plasmacytosis is a rare disorder characterized by cutaneous polyclonal plasma cell infiltration frequently associated with polyclonal hypergammaglobulinemia and lymphadenopathy. We report a case of a 67-year-old woman with an inflammatory ulcerated plaque in the left masseter region. A skin biopsy showed dense perivascular infiltrate of mature plasma cells in the dermis without atypia and immunoglobulin light chain restriction. After physical examination and further investigation, we ruled out systemic disease. Our patient was successfully treated only with hydrocortisone cream application. Few cases of isolated benign primary cutaneous plasmacytosis have been described, particularly in children. After excluding the diagnosis of a reactive process to an infection, which is unlikely in this case, we suspected of a rare manifestation of primary cutaneous plasmacytosis in adults with distinct presentation and clinical course.